Pengaruh Tanggung Jawab Sosial Perusahaan (Corporate Social Responsibility) dan Budaya Organisasi terhadap Kepuasan Kerja dan Kinerja Bisnis (Studi pada BUMN dan BUMD di Propinsi Riau) - Sri Indarti (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research builds an integrative model which aims to provide an overall interpretation on how the contribution of Corporate Social Responsibility (CSR), organizational culture, and work satisfaction influence business performance. This study is conducted at BUMN and BUMD in the Riau Province by using primary and secondary data. The samples are employees of BUMN and BUMD of Riau province consisting of 272 respondents. Sampling technique uses purposive sampling and simple random sampling and using path analysis. The result shows that strong organizational culture, which has a relationship with CSR is able to increase work satisfaction and business performance of BUMN and BUMD, however, in terms of business performance, BUMN and BUMD have not been optimal as expected because of stronger focus on external compared with the internal focus. Similarly, the implementation of CSR is able to increase the performance of BUMN and BUMD. Organizational culture has a significant role in influencing work satisfaction, and business performance but not for CSR. Since the CSR is the policy of the central BUMN and aimed to contribute for external stakeholders, therefore the branch office of BUMN in Riau Province just implement it without employees’participation the same reason also occurs at BUMD.Keywords: CSR, Organizational Culture, Work satisfaction, and Business Performance